Challenges facing the elimination of sleeping sickness in west and central Africa: sustainable control of animal trypanosomiasis as an indispensable approach to achieve the goal. Issue 1 (December 2015) - Simo, Gustave; Rayaisse, Jean
Abstract African trypanosomiases are infectious diseases caused by trypanosomes. African animal trypanosomiasis (AAT) remains an important threat for livestock production in some affected areas whereas human African trypanosomiasis (HAT) is targeted for elimination in 2020. In West and Central Africa, it has been shown that the parasites causing these diseases can coexist in the same tsetse fly or the same animal. In such complex settings, the control of these diseases must be put in the general context of trypanosomiasis control or "one health" concept where the coordination of control operations will be beneficial for both diseases. In this context, implementing control activities on AAT will help to sustain HAT control. It will also have a positive impact on animal health and economic development of the regions. The training of inhabitants on how to implement and sustain vector control tools will enable a long-term sustainability of control operations that will lead to the elimination of HAT and AAT.